Chest-wall contouring surgery in female-to-male transgender patients: A one-center retrospective analysis of applied surgical techniques and results. (March 2017) - Kääriäinen, M.; Salonen, K.; Helminen, M.; Karhunen-Enckell, U.
Background and Aims: Chest-wall contouring surgery is an important part of the gender reassignment process that contributes to strengthening the self-image and facilitating living in the new gender role. Here, we analyze the surgical techniques used in our clinic and report the results. Material and Methods: Female-to-male transgender patients (n = 57) undergoing chest-wall contouring surgery at Tampere University Hospital between January 2003 and April 2015 were enrolled in the study. Breast appearance was evaluated and either a concentric circular approach or a transverse incision technique was used for mastectomy. Patient characteristics and data regarding the technique and postoperative results were collected and analyzed retrospectively. Results: In addition to the transgender diagnosis, 40.4% of the patients had another psychiatric diagnosis. For mastectomy, a concentric circular approach was used in 50.9% and a transverse incision approach in 49.1% of the patients. In the transverse incision group, 21.4% of the patients underwent pedicled mammaplasty and 78.6% mastectomy with a free nipple–areola complex graft. Compared with the transverse incision group, breasts were smaller (p < 0.001) and body mass index value was lower in the concentric circular group (p = 0.001). One-third of the patients had complications (hematoma, infection, seroma, fistula, or partial necrosis of nipple–areola complex) and the reoperation rate was 8.8%. Hematoma was the most frequent reason for reoperation. Corrections were required for the scar in 14.0% of the patients, the contour in 28.0%, the areola in 15.8%, and the nipple in 5.3%. Secondary corrections were needed more often in the concentric circular (55.2%) than in the transverse incision group (25.0%; p = 0.031). Conclusions: The larger the breast, poorer the skin quality, and greater the amount of excess skin, the longer the required incision and resulting scar is for mastectomy of female-to-male patients. Hematoma is the most common reason for acute reoperation and secondary corrections are often needed.